2014
DOI: 10.1155/2014/903014
|View full text |Cite
|
Sign up to set email alerts
|

XB130—A Novel Adaptor Protein: Gene, Function, and Roles in Tumorigenesis

Abstract: Several adaptor proteins have previously been shown to play an important role in the promotion of tumourigenesis. XB130 (AFAP1L2) is an adaptor protein involved in many cellular functions, such as cell survival, cell proliferation, migration, and gene and miRNA expression. XB130's functional domains and motifs enable its interaction with a multitude of proteins involved in several different signaling pathways. As a tyrosine kinase substrate, tyrosine phosphorylated XB130 associates with the p85α regulatory sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Bioinformatics analysis has shown that the top diseases and cellular functions related to XB130 are cancers and cell growth, respectively 11 . Therefore, XB130 has been predicted to be an oncogene and a potential diagnostic marker and therapeutic target for cancers 3,4 . But after that, in 2019, XB130 has been reported to be a tumor suppressor in skin tumorigenesis induced by carcinogen through inhibiting inflammation, 12 which was in contrast with previous conclusions and indicated that XB130 may play different roles in different tumors.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Bioinformatics analysis has shown that the top diseases and cellular functions related to XB130 are cancers and cell growth, respectively 11 . Therefore, XB130 has been predicted to be an oncogene and a potential diagnostic marker and therapeutic target for cancers 3,4 . But after that, in 2019, XB130 has been reported to be a tumor suppressor in skin tumorigenesis induced by carcinogen through inhibiting inflammation, 12 which was in contrast with previous conclusions and indicated that XB130 may play different roles in different tumors.…”
Section: Introductionmentioning
confidence: 86%
“…XB130, also known as actin filament associated protein 1‐like 2, is a novel multifunctional adapter protein 3‐5 . First, XB130 crosslinks actin filaments (F‐actin), promoting cell endocytosis, migration, and invasion 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XB130, an adaptor protein, is discovered in the molecular cloning of actin filament‐associated protein (AFAP) . Adapter proteins are a unique group of protein binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…Several scaffold proteins have been implicated in the regulation of cell migration, such as the growth factor receptor-bound protein (Grb) family, tyrosine kinase substrate (Tks) family and non-catalytic region of tyrosine kinase adaptor protein (Nck) family [4-6]. XB130 is a scaffold protein that belongs to the actin filament associated protein family and acts as a signal transduction molecule to mediate cell growth, survival and cytoskeleton remodeling [7]. …”
Section: Introductionmentioning
confidence: 99%